UTERINE RUPTURE: A REVIEW OF 34 CASES AT AYUB TEACHING HOSPITAL ABBOTTABAD - Khan, Sameera; Parveen, Zahida; Begum, Shamshad; Alam, Iqbal (Journal of Ayub Medical College Abbottabad, 2003)
Background: Uterine rupture is a deadly obstetrical emergency endangering the life of both mother and fetus. This descriptive study was conducted to determine the frequency of ruptured uterus at Ayub Teaching Hospital Abbottabad and to elicit possible causes/reasons of ruptured uterus. Methods: The study was conducted at the department of Obstetrics & Gynaecology, Ayub Teaching Hospital, Abbottabad, Pakistan over a period of one year from July 1st, 2001 to June 30th, 2002. All cases of uterine rupture presenting during the study period were recorded and managed in the department using a protocol prepared for the purpose of this study. Data was recorded on pre-designed Proforma. Results: There were 34 cases of ruptured uterus out of a total of 3435 deliveries (including 1128 Caesarian sections) over a one-year time period (incidence of 1/100 deliveries) with 31 intra-partum deaths. The most common age group was from 31-35 years (16/34, 47%), followed by the 26-30 years age group (13/34, 38.2%). A majority (29/34, 85.3%) were cases of unscarred uterus presenting with rupture; the most common cause of rupture in all cases was inappropriate injections of Oxytocin (11/34, 32.35%), followed by obstructed labour (9/34, 26.5%). All were anemic and most of them were in shock. Conclusion: The leading cause of ruptured uterus was found to be mismanagement by traditional birth attendants. We can reduce maternal mortality due to rupture uterus by giving proper training to traditional birth attendants and by mass education through electronic media. Key words: Rupture Uterus, Obstructed Uterus, Traditional birth Attendants, Mother and child health care.